TOWARD ESTABLISHING A SUSTAINABLE TOURISM ON THE TALIMBARU VILLAGE IN THE KARO REGENCY - Herliani, Rini; Zainal, Andri (Journal of Community Research and Service, 2019)
This article aims to present a descriptive analysis related to the Embung Talimbaru Ecotourism Area (ETEA). The development of this ETEA refers to the actualization of the Talimbaru Village Mid-Term Development Plan (RPJMD) for 2016-2021 which has the potential for the realization of an ecotourism area that is not only suitable to support the Lake Toba Geopark Area, but also as the next New Bali program. Previous studies have highlighted the importance of strengthening the capacity of local communities in the development of community-based tourism that was characteristic of the previous era of tourism in Karo District. The priority issues that underline the importance of implementing business management and good governance in Village Owned Enterprise (known as BUMDES) activities, especially with the acceleration of the management of the ETEA as a leading local nature tourism object. In addition, the success of the sustainable management of the ETEA will be largely determined by the competence and professionalism of the human resources and infrastructure of the associated tourism village management ecosystem. Strategic actualization of the embodiment of a descriptive approach to the development of ETEA is presented in detail in the discussion segment toward preparing for Community Service program in both mono and multi-year schemes. Keywords: community-based tourism; descriptive approach; Embung Talimbaru Ecotourism Area; Community Service Program; Karo.